2018
DOI: 10.1021/acs.chemmater.8b02105
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Blende Magnesium Sulfide in Rechargeable Magnesium-Sulfur Batteries

Abstract: Magnesium-sulfur batteries are one of the most promising next-generation battery systems due to their high energy density, low cost, and high level of safety. However, the reaction mechanisms are not well understood, and in particular, the discharge reaction products have not yet been identified. Here we show that zinc blende magnesium sulfide is observed as a reaction product after discharging in magnesium-sulfur batteries. When magnesium reacts electrochemically with sulfur in a sulfone-based magnesium elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…In a recent report, Nakayama et al also observed the formation of a metastable zinc blende MgS phase during the discharge of a sulfur cathode in a Mg/S battery with sulfone-based magnesium electrolyte. 23 This, together with our experimental and computational ndings, makes us conclude that the nal discharge product is indeed MgS in the zinc blende structure type. For further comparison, we determined the theoretical average discharge voltage for the conversion of hcp-Mg and rhombic sulfur into the zinc blende MgS from our DFT calculations.…”
Section: àsupporting
confidence: 53%
See 1 more Smart Citation
“…In a recent report, Nakayama et al also observed the formation of a metastable zinc blende MgS phase during the discharge of a sulfur cathode in a Mg/S battery with sulfone-based magnesium electrolyte. 23 This, together with our experimental and computational ndings, makes us conclude that the nal discharge product is indeed MgS in the zinc blende structure type. For further comparison, we determined the theoretical average discharge voltage for the conversion of hcp-Mg and rhombic sulfur into the zinc blende MgS from our DFT calculations.…”
Section: àsupporting
confidence: 53%
“…5 Nakayama et al investigated the charge/discharge reaction mechanism of a Mg/S cell with sulfone-based magnesium electrolytes by various ex situ techniques like XPS, X-ray absorption near edge structure (XANES) spectroscopy, XRD, high-energy XRD (HE-XRD), transmission Xray microscopy (TXM) and solid-state NMR. 23 These studies conclude that MgS with the zinc blende (ZB) structure type forms as the nal discharge product on the cathode side. In another report, Robba et al investigated the reduction processes in Mg/S cells with Mg(TFSI) 2 -MgCl 2 electrolyte by operando XRD and S K-edge X-ray absorption (XANES) studies.…”
Section: Introductionmentioning
confidence: 96%
“…However, while the barriers for decomposition of the sulfones are lower than those of the glymes, they are still significantly large, indicating sulfone stability should be attainable if the relevant electrolyte interactions are controlled. To our knowledge, the only documented examples of high Mg plating Coulombic efficiency (>90%) in sulfone solvents have utilized MgCl 2 as the primary salt and in most cases require an ether co-solvent (Kang et al, 2017; Merrill and Schaefer, 2018; Nakayama et al, 2018). Because of the significant Mg 2+ complexation and interfacial activation tendencies of the Cl − anion (Shterenberg et al, 2015, 2017), these examples suggest that stabilization of a sulfone solvent is possible if the electrolyte composition is rationally designed such that the solvent is less exposed to the Mg + cation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, MgS was found to be electrochemically virtually inactive in the chosen electrolyte. Recently, Nakayama et al elucidated the nature of the phase of the formed MgS after discharge, which is metastable zinc blende MgS rather than the rock salt phase. The high stability of both Mg 3 S 8 and MgS was made responsible for the high polarization and the unclear charge plateaus …”
Section: Cathode Materialsmentioning
confidence: 99%
“…Copyright 2017, American Chemical Society. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%